Investigating the global stakeholder engagement process that informed the development of the Key Biodiversity Area Standard - Maxwell, Jessica Lynch (The University of Edinburgh, 2017)
This thesis investigated the development of the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), which is a new approach to identifying important sites for biodiversity. Key Biodiversity Areas are defined as sites contributing significantly to the global persistence of biodiversity. The KBA Standard was developed through a global stakeholder engagement process convened by the International Union for Conservation of Nature’s Joint Task Force on Biodiversity and Protected Areas (IUCN Task Force). The engagement process included four main components: (i) technical workshops with subject experts; (ii) interviews and an online questionnaire with end-users; (iii) regional events with additional interested stakeholders; and (iv) an open online consultation where stakeholders were invited to review the draft KBA Standard. The aim of this thesis was to use an action research approach to work with the IUCN Task Force to analyse the end-user component of the global stakeholder engagement process. End-users were defined during the engagement process as those who lead or influence decision-making processes linked to mechanisms that secure biodiversity or that avoid biodiversity loss. The main objectives of this research were to: (i) clarify the purpose of engaging end-users by examining the use of normative, instrumental, and substantive rationales; (ii) use mixed methods to gain an understanding of end-users’ needs and concerns; (iii) categorise and analyse end-users’ needs and concerns by sector and region; (iv) assess the end-user engagement process through a summative evaluation; (v) examine how end-user input was used to inform the development of the KBA Standard; and (vi) develop a set of recommendations related to global end-user engagement practice. The analysis indicated that the IUCN Task Force used a blend of instrumental and substantive rationales to justify engaging end-users. Five main categories of end-user needs and concerns emerged from the analysis of the qualitative interview data: (i) the need for communication and local stakeholder engagement; (ii) the potential for the KBA Standard to either complement or conflict with existing approaches; (iii) the need for clarity regarding the scale at which KBAs can be identified (i.e. global, regional, and/or national); (iv) concerns about the implementation of the KBA Standard, including data availability, timeliness, and resources; and (v) comments about how KBAs inform decision-making, including management options, sustainable use, and prioritisation. These topics were examined in depth through the qualitative interviews and in breadth through the quantitative questionnaire. The results demonstrate a high level of convergence in opinion on many topics; however, four topics resulted in a divergence in opinion between end-users, including: (i) the scale at which KBAs are identified; (ii) the prioritisation of KBAs over other areas; (iii) whether KBA data should be made freely available; and (iv) whether development activities should be permitted in KBAs. These areas of divergence were analysed further by categorising end-user questionnaire responses by sector and region. The results have important implications for how end-users are identified, categorised, and engaged and highlight the complex and individual nature of end-users’ needs and concerns. The summative evaluation analysed the purpose, process, outputs, and outcomes against a typology of engagement and principles of good practice for international standard setting to reflect upon how end-users’ needs and concerns were integrated into the development of the KBA Standard. This indicated both the strengths and weaknesses of the engagement approaches used and informed the development of 11 recommendations to inform future similar processes. This thesis ultimately helps to bridge the gap between stakeholder engagement theory and practice and provides insight into the challenges and benefits of using a mixed methods action research approach to investigate a global stakeholder engagement process.
Keywords: global stakeholder engagement; end-users; key biodiversity areas; biodiversity conservation; action research